1989
DOI: 10.1002/yea.320050411
|View full text |Cite
|
Sign up to set email alerts
|

Physiology of mutants with reduced expression of plasma membrane H+‐ATPase

Abstract: Two mutations containing insertions and deletions in the promoter in the plasma membrane H+-ATPase gene (PMA1) of Saccharomyces cerevisiae have been introduced into the genome by homologous recombination, replacing the wild-type gene. The resulting strains have 15 and 23% of the wild-type ATPase content. Decreased levels of ATPase correlate with decreased rates of proton efflux and decreased uptake rates of amino acids, methylamine, hygromycin B and tetraphenylphosphonium. This supports a central role of the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
92
0
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(95 citation statements)
references
References 45 publications
(46 reference statements)
2
92
0
1
Order By: Relevance
“…14 C]methylammonium uptake as an indicator of membrane potential (35,36). As expected, wild type cells preincubated with protonophore carbonyl cyanide p-chlorophenylhydrazone displayed a significant reduction in methylammonium uptake compared with untreated cells (Fig.…”
Section: Hor7 Overexpression Causes a Depolarization Of The Plasma Mesupporting
confidence: 75%
See 2 more Smart Citations
“…14 C]methylammonium uptake as an indicator of membrane potential (35,36). As expected, wild type cells preincubated with protonophore carbonyl cyanide p-chlorophenylhydrazone displayed a significant reduction in methylammonium uptake compared with untreated cells (Fig.…”
Section: Hor7 Overexpression Causes a Depolarization Of The Plasma Mesupporting
confidence: 75%
“…Overexpression of Hor7p, on the other hand, conferred an increased resistance to Na ϩ and sensitivity to low pH. Moreover, Hor7p-overproducing cells displayed a decreased uptake of methylammonium, an indicator of the plasma membrane potential (35,36). The latter finding suggests that Hor7p overexpression causes a depolarization of the plasma membrane.…”
Section: Fig 6 Hor7 Overexpression Causes a Growth Defect At Low Phmentioning
confidence: 94%
See 1 more Smart Citation
“…As illustrated above, the P-type ATPases serve as effective therapeutic targets for clinically important problems. The fungal plasma membrane H + -ATPase is a proton pump that helps regulate intracellular pH (Sanders et al, 1981;Vallejo and Serrano, 1989) and maintains the transmembrane electrochemical proton gradient necessary for nutrient uptake (Prasad, 1991;Serrano, 1989). It is an essential enzyme (Serrano et al, Fink, 1986) consisting of a single large polypeptide subunit of Mr ~100 kDa that represents approximately 25% percent of the total plasma membrane protein.…”
Section: A New Mechanistic Classmentioning
confidence: 99%
“…The results are means f SD of 4 experiments We observed that addition of cycloheximide to glucose growing yeast gave rise to an inactivation of the ATPase that occurred at a lower rate than the one observed in the case of the K' transport system. To investigate the effect that these changes in ATPase could produce in the K' transport activity we used two mutants with a reduced expression of plasma membrane ATPase [16] and found that a decrease in the activity of this enzyme of as much as 60% was accompanied by a decrease in the activity of the carrier of only 25% (Table I). Similar results have been reported by Ramos et al [12].…”
Section: Resultsmentioning
confidence: 99%